Age-Related Immune Profile of the T Cell Receptor Repertoire, Thymic Recent Output Function, and miRNAs. (4th December 2020) - Xu, Yan; Xu, Ling; Chen, Cunte; Zhang, Yikai; Zeng, Chengwu; Jin, Zhenyi; Chen, Shaohua; Li, Bo; Zha, Xianfeng; Yin, Zhinan; Li, Yangqiu
Abstract : Background . T cell immunity plays a central role in the body's defense system, including maintaining homeostasis and preventing tumorigenesis and viral infection. Immune system functions degenerate with age, leading to immune senescence. Physiologically, immune senescence is characterized by a decrease in T cell receptor diversity, naive T cell deficiency, and alterations in T cell immune-related miRNAs. However, little is known about the characteristics of T cell immunosenescence in Chinese individuals. Results . A significant decrease in the miR-17, miR-92a, and miR-181a levels in PBMCs was detected with age. The miR-92a and miR-181a levels were upregulated in CBMCs when comparing healthy individuals to group I (0 9 years), whereas miR-17 was downregulated. The sjTREC level in PBMCs was negatively correlated with age, and a sharp decrease in sjTRECs was found between groups I and II (10 19 years). Twenty-four TCR V β subfamilies could be detected in most samples, and most displayed polyclonality, while skewed expression of the V β subfamilies as well as an increased oligoclonal tendency was found with age. Similarly, the frequencies of the TCR V γ and V δ subfamilies decreased with age, and the alteration in clonality appeared to be stable at different ages. Conclusion . We made the novel observation of T cell immunosenescence with age in Chinese individuals, which may provide information for immune targets to enhance the T cell immune response in immunotherapy settings for elderly patients.